Treatment of a patient with Kawasaki disease associated with selective IgA deficiency by continuous infusion of cyclosporine A without intravenous immunoglobulin - Anzai, Tatsuya; Minami, Takaomi; Sato, Tomoyuki; Furui, Sadahiro; Yamagata, Takanori (The Turkish Journal of Pediatrics, 2016)
Intravenous immunoglobulin therapy is standard for Kawasaki disease (KD) treatment; however, anaphylactic reactions to immunoglobulins are a risk in KD patients with selective IgA deficiency (sIgAD). The therapy for KD associated with sIgAD has not been established. The IgA immune response is believed to play an important role in KD vasculitis. We report the case of a 5-year-old boy with KD and sIgAD treated with intravenous cyclosporine A (CsA, 3.0 mg/kg/day) instead of intravenous immunoglobulin (IVIG). The fever and inflammation immediately resolved without a coronary artery lesion. In KD patients with sIgAD, we believe that an IgA immune response is lacking, which is the reason for milder KD symptoms than in those without sIgAD. This case report aids in clarifying the role of IgA antibodies in KD and provides evidence that CsA is a potential candidate for first-line therapy for patients with KD with contraindications to IVIG.